Propofol-Based Total Intravenous Anesthesia is Associated with Better Survival than Desflurane Anesthesia in Epithelial Ovarian Cancer Surgery: A Retrospective Cohort Study - Tseng, Wei-Cheng; Lee, Meei-Shyuan; Lin, Ying-Chih; Lai, Hou-Chuan; Yu, Mu-Hsien; Wu, Ke-Li; Wu, Zhi-Fu (Frontiers in Pharmacology, 2021)
Background: Previous studies have shown that anesthetic techniques can affect outcomes of cancer surgery. We investigated the association between anesthetic techniques and patient outcomes after elective epithelial ovarian cancer surgery. Methods: This was a retrospective cohort study of patients who received elective open surgery for epithelial ovarian cancer between January 2009 and December 2014. Patients were grouped according to the administration of propofol or desflurane anesthesia. Kaplan–Meier analysis was performed, and survival curves were constructed from the date of surgery to death. Univariate and multivariate Cox regression models were used to compare hazard ratios for death after propensity matching. Subgroup analyses were performed for age, body mass index, preoperative carbohydrate antigen-125 level, International Federation of Gynecology and Obstetrics staging, and operation and anesthesia time. Results: In total, 165 patients (76 deaths, 46.1%) who received desflurane anesthesia and 119 (30 deaths, 25.2%) who received propofol anesthesia were eligible for analysis. After propensity matching, 104 patients were included in each group. In the matched analysis, patients who received propofol anesthesia had better survival with a hazard ratio of 0.52 (95% confidence interval, 0.33–0.81; P = 0.005). Subgroup analyses also showed significantly better survival with old age, high body mass index, elevated carbohydrate antigen-125 level, advanced International Federation of Gynecology and Obstetrics stage, and prolonged operation and anesthesia time in the matched propofol group. In addition, patients administered with propofol anesthesia had less postoperative recurrence and metastasis than those administered with desflurane anesthesia in the matched analysis. Conclusion: Propofol anesthesia was associated with better survival in patients who underwent elective epithelial ovarian cancer open surgery. Prospective studies are warranted to evaluate the effects of propofol anesthesia on oncological outcomes in patients with epithelial ovarian cancer.